2010
DOI: 10.1159/000289206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Furosemide on Ductal Closure and Renal Function in Indomethacin-Treated Preterm Infants during the Early Neonatal Period

Abstract: Background: Furosemide is known to increase renal prostaglandin synthesis. However, its influence on ductal closure and renal toxicities of indomethacin in preterm infants has not been conclusive, especially during the early neonatal period. Objectives: To identify the effects of furosemide after indomethacin administration on the rate of patent ductus arteriosus (PDA) closure and renal function in preterm infants. Methods: 68 infants (gestational age <34 weeks and birth weight <2,000 g) receiving indomethacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 57 publications
(43 reference statements)
0
19
1
1
Order By: Relevance
“…Lee et al [108] identified the effects of furosemide, after indomethacin administration on the rate of patent ductus arteriosus closure and renal function, in preterm infants with a gestational age <34 weeks and a birthweight <2,000 g receiving indomethacin therapy (one course: 0.2–0.1–0.1 mg/kg every 12 h) mostly started <48 h after birth. Thirty-five infants received furosemide (1 mg/kg) and 33 infants were the controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [108] identified the effects of furosemide, after indomethacin administration on the rate of patent ductus arteriosus closure and renal function, in preterm infants with a gestational age <34 weeks and a birthweight <2,000 g receiving indomethacin therapy (one course: 0.2–0.1–0.1 mg/kg every 12 h) mostly started <48 h after birth. Thirty-five infants received furosemide (1 mg/kg) and 33 infants were the controls.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of acute renal failure (serum creatinine >1.6 mg/dL) was greater in the furosemide group (59%) than in the control group (10%; p < 0.001). Lee et al [108] conclude that the use of furosemide in combination with indomethacin increased the incidence of acute renal failure but did not affect the patent ductus closure rate in preterm infants.…”
Section: Resultsmentioning
confidence: 99%
“…Furosemide administration and phototherapy also have been reported to increase the incidence of PDA (19, 20); however, more recent studies have not found this to be the case (21, 22). Administration of exogenous surfactant can alter the presentation of a PDA.…”
Section: Incidence Of Spontaneous Ductus Closurementioning
confidence: 99%
“…In a study of 68 preterm infants treated with indomethacin and were randomly assigned to receive furosemide (1 mg/kg) or placebo, there was no difference in the rate PDA closure, neonatal morbidity, or mortality in the furosemide-treated group [120]. …”
Section: How To Treat?mentioning
confidence: 99%